2015
DOI: 10.1080/1754730x.2015.1037848
|View full text |Cite
|
Sign up to set email alerts
|

Clearing hurdles: the challenges of implementation of mental health evidence-based practices in under-resourced schools

Abstract: Schools have become the main provider of services to children with mental health needs. Although there is substantial literature on barriers to implementation of evidence-based practices (EBPs) in under-resourced school districts, less has been written on how to overcome those barriers. Providing mental health services in the school setting presents a tremendous opportunity to increase access to quality mental health care for underserved youth. This review provides a brief overview of the barriers to successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 68 publications
3
58
1
Order By: Relevance
“…Participants noted that they often worked on a team of staff members, each serving unique roles, in order to meet the diverse needs of students with autism. Engaging the entire school team may be an important first step, in order to identify which staff members would be the most appropriate candidates to serve as implementers (Eiraldi, Wolk, Locke, & Beidas, 2015). In addition, given time and staffing constraints in schools, EBPs that align with children’s individual social and academic goals are likely to be more successfully implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Participants noted that they often worked on a team of staff members, each serving unique roles, in order to meet the diverse needs of students with autism. Engaging the entire school team may be an important first step, in order to identify which staff members would be the most appropriate candidates to serve as implementers (Eiraldi, Wolk, Locke, & Beidas, 2015). In addition, given time and staffing constraints in schools, EBPs that align with children’s individual social and academic goals are likely to be more successfully implemented.…”
Section: Discussionmentioning
confidence: 99%
“…As some studies have demonstrated, lack of parent participation in research studies conducted in underresourced schools does not have to be endemic (Gross, Breitenstein, Eisbach, Hoppe, & Harrison, 2014). Studies have shown that effective engagement strategies with low-income families include (a) acknowledging parents’ values and their expertise about their children, (b) acknowledging that they want to be good parents, (c) reinforcing parents for their efforts to change, and (d) giving them options for achieving intervention goals (Eiraldi et al, 2015; Gross et al, 2014). Motivation strategies include eliciting self-motivating change statements and identifying, developing, and executing plans for dealing with barriers to treatment adherence and continued participation in treatment sessions (Nock & Kazdin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Schools are one of the main venues for the delivery of mental health services to children (Rones & Hoagwood, 2000) and may be the ideal context in which to implement evidence-based interventions (EBIs; Eiraldi, Benjamin Wolk, Locke, & Beidas, 2015). Services are offered in convenient locations and are provided at little or no cost to families (Taras, 2004).…”
mentioning
confidence: 99%
“…Studies of the effectiveness of mental health interventions have yielded disappointing results in under‐resourced urban schools (e.g., Farahmand, Grant, Polo, Duffy, & DuBois, ). The causes are likely multifaceted and might include problems with the adequacy of the intervention, the severity of individual student problems, and lack of training for those delivering the interventions (Eiraldi, Benjamin Wolk, Locke, & Beidas, ). Schools seldom employ mental health EBPs, but when they do, the interventions are often implemented with low fidelity (Farahmand et al, ).…”
Section: Implementing Mental Health Supports In Urban Schoolsmentioning
confidence: 99%
“…School‐based clinicians rarely receive adequate training and support on EBP implementation. This greatly contributes to low fidelity (Eiraldi et al, ). Also, students in low‐income urban schools often present with more severe problems and comorbid conditions than students in nonurban settings (Farahmand et al, ).…”
Section: Implementing Mental Health Supports In Urban Schoolsmentioning
confidence: 99%